Immunologic responses to a novel DNA vaccine targeting human papillomavirus‐11 E6E7. (17th July 2017) - Ahn, Julie; Peng, Shiwen; Hung, Chien‐Fu; Roden, Richard B. S.; Wu, Tzyy‐Choou; Best, Simon R.
Abstract : Objectives/Hypothesis: Recurrent respiratory papillomatosis (RRP) is a benign disease caused by human papillomavirus (HPV) types 6 and 11. Although a prophylactic vaccine against RRP is available, a therapeutic vaccine is needed to treat those already infected. The objective of our study was to design and test a DNA vaccine targeting HPV11 proteins. Study Design: Preclinical scientific investigation. Methods: A DNA vaccine encoding the HPV11 E6 and E7 genes linked to calreticulin (CRT) was generated. Immunologic response to the HPV11 CRT/E6E7 vaccine was measured by vaccinating C57BL/6 mice via electroporation and measuring CD8 + T cell responses from harvested splenocytes. A tumor cell line containing HPV11‐E6E7 was created, and the ability of novel DNA vaccine to control tumor growth was measured in vivo. Results: Our vaccine generated a significant and specific CD8 + T‐cell response against the HPV11‐E6aa41‐70 peptide. The CD8 + T‐cell responses did not recognize E7 epitopes, indicating E6 immunodominance. CD8 + responses were augmented in the CRT‐linked vaccine compared to a control non‐CRT vaccine. The HPV11 CRT/E6E7 vaccine was used to treat mice inoculated with a HPV11 E6E7 expressing tumor cell line after temporary CD3 depletion to facilitate tumor growth. Vaccinated mice had a significantly lower tumor growth rate ( P = .029) and smaller tumor volumes compared to control mice, indicating an augmented immunologic response in vaccinated mice. Conclusions: A DNA vaccine targeting HPV11 E6E7 generates a specific HPV11 CD‐8 + T‐cell response capable of reducing the growth of HPV11‐expressing tumors. DNA vaccines are a promising immunologic strategy for treating RRP. Level of Evidence: NA. Laryngoscope, 127:2713–2720, 2017